Separation of polar compounds using poly(ethylene oxide) bonded stationary capillary liquid chromatography - Roza Linda; Abdullah; Mohamad Rafi; Aster Rahayu; Lee, Lee Wah; Takeuchi, Toyohide (Penerbit Universiti Kebangsaan Malaysia, 2021)
Poly(ethylene oxide) (PEO) bonded stationary phase has been synthesized by a single and simple step reaction. Poly(ethylene glycol monomethyl ether p-toluene sulfonate) (tosylated-PEO, molecular weight 900, n ≈ 18) was chemically bonded to 3-aminopropyl silica (TSKgel NH2-60, 5 μm particle size, and 60 Å mean pore diameter). The prepared stationary phase was able to separate polar compounds such as phenolics and nucleobases in capillary liquid chromatography. The retention and separation of phenolics and nucleobases could be achieved under isocratic elution condition. Nucleobases such as thymine, adenine, uracil, uridine, cytidine and toluene and phenolics (phenol, pyrocatechol, pyrogallol) were baseline separated in less than 6 min using 98% acetonitrile and less than 7 minutes using 80% acetonitrile, respectively. We demonstrated that the retention of nucleobases as analyte decreased with decreasing eluent concentration. The retention of these polar compounds was believed to be based on dipole-dipole and/or hydrogen-bonding interactions.